2016
DOI: 10.1111/jpn.12539
|View full text |Cite
|
Sign up to set email alerts
|

Energy and protein requirements of weaned male and female Saanen goats

Abstract: The objective of this research was to estimate the energy and protein requirements for maintenance and growth in male (castrated and intact) and female Saanen goat kids between 15 and 30 kg BW. To determine the net energy requirements for maintenance (NE ) and the net protein requirements for maintenance (NP ), 75 goats (25 castrated and 26 intact males and 24 females) were used. Twenty-one goats (seven castrated and eight intact males and six females) were randomly assigned for slaughter to estimate the initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
21
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 24 publications
7
21
1
1
Order By: Relevance
“…The DMI of goats fed ad libitum was on average 63.0% greater (P < 0.01) than for those fed 1.2 × L (Table 3), throughout the entire experimental period. For instance, observed DMI (3% BW) was lower than the 4% BW predicted by the AFRC (1998), but similar to that reported previously for Saanen kids (FIGUEIREDO et al, 2017). 1 n = number of animals subjected to the metabolism trial; BW = body weight; DMI = dry matter intake; CPI = crude protein intake; GEI = gross energy intake; MEI = metabolizable energy intake; DDM = digestibility of dry matter; DCP = digestibility of crude protein; DGE = digestibility of gross energy and q = metabolizability (ME/GE).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The DMI of goats fed ad libitum was on average 63.0% greater (P < 0.01) than for those fed 1.2 × L (Table 3), throughout the entire experimental period. For instance, observed DMI (3% BW) was lower than the 4% BW predicted by the AFRC (1998), but similar to that reported previously for Saanen kids (FIGUEIREDO et al, 2017). 1 n = number of animals subjected to the metabolism trial; BW = body weight; DMI = dry matter intake; CPI = crude protein intake; GEI = gross energy intake; MEI = metabolizable energy intake; DDM = digestibility of dry matter; DCP = digestibility of crude protein; DGE = digestibility of gross energy and q = metabolizability (ME/GE).…”
Section: Resultssupporting
confidence: 89%
“…As expected, the intercept estimate did not differ from zero (P = 0.67). The same value was reported by Figueiredo et al (2017) and is within the wide range of values for k g reported in the literature; i.e., 0.30 to 0.65 (REID et al, 1980). Because protein deposition efficiency is lower than that reported for fat, varying from 0.1 to 0.40 for protein and from 0.60 to 0.84 for fat (ARC, 1980), goats depositing more protein than fat (e.g., intact males, growing animals) have lower k g .…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Em outros estudos também foi verificada menor deposição de lipídeos em função da redução na ingestão de energia (BEZERRA et al, 2010;LISBOA et al, 2010;MARQUES et al, 2014). Mesmo em condição de restrição alimentar, os caprinos Canindé apresentaram deposição de gordura total no corpo superior à deposição em caprinos castrados da raça Saanen com pesos semelhantes (FIGUEIREDO, 2014), o que pode demonstrar a reserva energética como prioridade para as raças nativas e naturalizadas. Uma maior deposição de gorduras em raças nativas e naturalizadas também está atrelada a menores valores de energia líquida para mantença.…”
Section: Resultsunclassified
“…Different feeding systems indicate that intact males require more ME M 273 than females (ARC, 1980;CSIRO, 1990;NRC, 2000NRC, , 2007. Conversely, individual studies conducted with goats have generally concluded that sex affects energy requirements for growth, but it does not affect energy requirements for maintenance (Ash and Norton, 1987;Bompadre et al, 2014;Almeida et al, 2015;Figueiredo et al, 2017). Therefore, contradictory results have been reported.…”
Section: Introductionmentioning
confidence: 99%